The Influence of Digital Marketing and Tourist Motivation on Interest in Visiting the Lau Kawar Lake Tourist Attraction - Fransiska Khairani; Raihan Dafa Fahrezi; Selwendri Selwendri (Jurnal Multidisiplin Sahombu, 2026)
This study aims to analyze the influence of digital marketing and tourist motivation on visiting interest in the Lau Kawar Lake Tourist Destination, located in Karo Regency. The research employs a qualitative descriptive method with a literature review approach, examining previous studies related to the topic. The findings indicate that digital marketing plays a crucial role in shaping tourists’ positive perceptions through visual, interactive, and emotional promotions disseminated via social media and other digital platforms. Meanwhile, tourist motivation both internal drives, such as relaxation and new experiences, and external factors, such as natural beauty and local culture significantly strengthens the intention to visit. The synthesis of various studies reveals a synergistic relationship between digital marketing and tourist motivation in enhancing visiting interest. Therefore, the implementation of creative digital marketing strategies that align with tourists’ psychological needs becomes a key factor in attracting visitors to Lau Kawar Lake and improving the sustainable competitiveness of the regional tourism sector.